Aquaporin-3 Attenuates Oxidative Stress-Induced Nucleus Pulposus Cell Apoptosis Through Regulating the P38 MAPK Pathway - Xu, Yichun; Yao, Hui; Wang, Qiyou; Xu, Wenbin; Liu, Kaihua; Zhang, Junbin; Zhao, Huiqing; Hou, Gang (Cellular physiology and biochemistry, 2018)
Background/Aims: Previous studies have shown that oxidative damage is a main contributor to disc nucleus pulposus (NP) cell apoptosis. Aquaporin-3 (AQP-3) facilitates reactive oxygen species (ROS) scavenging and thus alleviates oxidative injury in other cells. This study aims to investigate the role and mechanism of AQP-3 in regulating NP cell apoptosis under oxidative damage. Methods: Rat NP cells were treated with H 2 O 2 for 48 hours, while control NP cells were free of H 2 O 2 . Recombinant AQP-3 lentiviral vectors were used to investigate the effect of enhanced AQP-3 expression levels in NP cells. NP cell apoptosis was assessed by flow cytometry, caspase-3 activity, gene expression of apoptosis-related molecules (Bax, Bcl-2 and caspase-3), and protein expression of cellular apoptosis markers (cleaved PARP and cleaved caspase-3). Additionally, intracellular ROS content and activity of the p38 MAPK pathway were evaluated. Results: Compared with the control NP cells, oxidative damage in the treatment cells significantly increased cell apoptosis ratios and caspase-3 activity, upregulated gene expression of Bax and caspase-3, downregulated gene expression of Bcl-2, and increased protein expression of cleaved PARP and cleaved caspase-3, as well as increased intracellular ROS content and activity of the p38 MAPK pathway. However, AQP-3 overexpression partly alleviated cell apoptosis, decreased intracellular ROS content, and inhibited the p38 MAPK pathway in NP cells under oxidative damage. Conclusion: Oxidative damage can significantly downregulate AQP-3 expression. Enhancing AQP-3 expression in NP cells partly attenuates cellular apoptosis through regulating the p38 MAPK pathway under oxidative damage.